Political Dimensions of Weaker Sections Welfare in Local Self Government in India: A Study - KRISHNA, VALMIKI RAMA; Venkatesha, Dr. Uddagatti (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Soon after independence, the main thrust of Indian Government centered on meeting the basic needs of India’s population which include food, clothing and shelter. With this perspective, the national policy makers looked at various measures to alleviate the rural poor. The process of self governance and planning by empowering the people through Panchayati Raj system although started nearly five decades earlier, but 73rd and 74th amendments in the Constitution of India brought an historic change in the process of decentralisation towards the grass root level and participation of people both in the formulation as well as implementation of the plans. The paper explores how the Constitution 73rd Amendment Act (1992), provided certainty, continuity and strength to the PRI’s for the welfare of the weaker sections through Decentralization. Uniform three-tier level of the village, block and district levels, direct elections to all seats and at all levels, indirect elections to chairpersons at intermediate and apex levels. Reservation on rotational basis for SC’s ST’s in proportion to their population, both for membership as well as Chairpersonships of the PRI’s. Not less than one third of the seats and offices reserved for women. The present paper intends to discuss the political participation of weaker sections in panchayat raj institutions in Karnataka in general and in Afjalpur taluk of Gulbarga District in particular as a case study. Finally the paper discusses about the political participation of weaker sections and sought their opinion of their involvement in the process of political, economic development and social justice, with the transfer of the list of Eleventh and the Twelfth Schedule of the Constitution to the rural and urban elected local bodies, and the process of welfare activities for weaker sections through the Panchayat Raj Institutions has been discussed.